Perspectives about adult sibling relationships: A dyadic analysis of siblings with and without intellectual and developmental disabilities. (January 2020) - Rossetti, Zachary; Lee, Chung eun; Burke, Meghan; Hall, Sarah
Highlights: Individuals with IDD and their siblings described having positive relationships. Individuals with IDD and their siblings enjoyed spending time together. Both siblings agreed about their perceptions of the context and quality of their sibling relationship. Individuals with Down syndrome and their siblings reported more reciprocal relationships. Individuals with Down syndrome and their siblings engaged in a wider variety of social activities. Abstract: Most siblings of individuals with intellectual and developmental disabilities (IDD) report positive sibling relationships. However, extant research often only examines the perspective of the nondisabled sibling; it is unclear whether siblings with IDD report close sibling relationships. Thus, the aim of this study was to understand adult sibling relationships from the perspectives of both siblings with and without IDD. Using dyadic interviews, we examined the perspectives of eight adult sibling dyads. The study was conducted in the United States. Data were analyzed using constant comparative analysis and cross-case analysis to identify themes within and across dyads. Overall, siblings with and without IDD reported enjoying spending time with one another. However, siblings with and without Down syndrome (versus autism spectrum disorder) reported more reciprocal sibling relationships, more frequent contact, and a greater range of shared activities. Implications for future research and practice are discussed.